ANALISIS PERBANDINGAN METODE WEIGHTED PRODUCT (WP) DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK PENDUKUNG KEPUTUSAN PEMILIHAN BIRO PERJALANAN PARIWISATA - Ryzal Pradito; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2014)
Decision Support System (DSS) is a system that helps managers to solve a semi-structured problem. There are techniques used to make the DSS, one of them is Fuzzy Logic Multi Criteria Decission Makaing (MCDM). Weigthed Product Method (WP) and Single Additive Weighting Method (SAW) is a method to solve the problem using multiplication to connect the atribute ratings, where rating attributes must be raised first with the weight relevant attributes weights. The applications results show comparison WP methods and SAW methods is closer to the value 1, so that the SAW method is the most appropriate method to solve the problem of the selection a trvel agency tourism.